RETROSPECTIVE EVALUATION OF THE CLINICAL COURSE OF PAGET’S DISEASE OF BONE - Hülya Hacişahinoğulları; Gamze Bilik Oyman; Gülşah Yenidünya Yalın; Özlem Soyluk Selçukbiricik; Nurdan Gül; Ferihan Aral; Refik Tanakol; Ayşe Kubat Üzüm (Sabiad)
Objective: Paget’s disease of bone (PDB) is a focal, chronic, metabolic disorder of bones and causes complications such as bone deformity, fractures, and heart failure. This study aimed to evaluate the clinical characteristics of patients with PDB and patients’ responses to antiresorptive treatments. Material and Methods: In the study, we retrospectively evaluated the medical records of patients who were followed up with PDB at the Istanbul Faculty of Medicine and treated with antiresorptive therapy. Results: A total of 26 patients (12 females/14 males) with PDB were evaluated. The mean age at diagnosis was 62.9±13.5 years. The median time from the onset of symptoms to diagnosis was 17.5 months (range 1-480). The symptoms were as follows: pain in 16, swelling in 3, rubor in 2, bone fracture in 1, nephrolithiasis in 1, and hearing loss in 1 patient. Laboratory tests revealed the following results (mean±SD); Alkaline phosphatase (ALP) 512±557 U/L, bone-specific ALP 81.2±51.4 µg/L, and the mean ALP was 4.12±4 times of upper limit of the normal range. The distribution of the disease was as follows: pelvis in 58%, vertebra in 46%, skull in 35%, femur in 23%, tibia in 11.5%, humerus in 3.8% of the patients. Of 26 patients, 21 were treated with zoledronic acid alone. Relapse occurred in four patients; the mean duration from therapy to relapse was 72.25±28.7 months. Conclusion: Zoledronic acid is a very potent antiresorptive drug and provides long-term remission of the disease even with a single dose of therapy.